PENGABDIAN MASYARAKAT PELAKSANAAN FISIOTERAPI PADA LOW BACK PAIN PADA PEKERJA BATIK DENGAN LATIHAN CORE STABILITY EXERCISE - Moh Fasekhatul Lisanudin; Andung Maheswara Rakasiwi (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2022)
Low back pain is a disorder that often occurs in everyday life and affects all individuals without exception. Low back pain (LBP) is a pain syndrome that occurs in the lower back and is a work related musculoskeletal disorder. A common problem for batik workers is pain in the lower back, the service carried out by batik workers in Sijambe Village Rt.02, Rw 01, Wonokerto District, Pekalongan Regency in the form of interviews with batik workers to observe physiotherapy problems in conditions of low back pain. The purpose of this activity is to increase knowledge and understanding of batik workers about the role of physiotherapy in batik workers, especially in preventing low back pain in batik workers. The solution offered by the team is to use counseling and training methods to prevent low back pain in batik workers with core stability exercise to prevent low back pain, the implementation of counseling activities is attended by batik workers. Prior to the counseling and training process, pre-test and post-test were given which became the benchmark for people who understood that the extension was carried out. The results of the pre test and post test proved that the level of understanding after being given counseling increased. The conclusion of the service activities carried out was that after being given physiotherapy counseling and physiotherapy interventions that there was a significant increase in knowledge of batik workers about the use of exercise therapy to prevent low back pain in batik workers. Keywods : Low Back Pain dan core stability exercise